2014
DOI: 10.1371/journal.pone.0103145
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Variability in the Genetically Uniform Forest Tree Species Pinus pinea L

Abstract: There is an increasing interest in understanding the role of epigenetic variability in forest species and how it may contribute to their rapid adaptation to changing environments. In this study we have conducted a genome-wide analysis of cytosine methylation pattern in Pinus pinea, a species characterized by very low levels of genetic variation and a remarkable degree of phenotypic plasticity. DNA methylation profiles of different vegetatively propagated trees from representative natural Spanish populations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 69 publications
(83 reference statements)
4
38
0
6
Order By: Relevance
“…A remarkable phenotypic plasticity in functional traits has also been described for stone pine when grown under restricted water availability conditions (Sánchez-Gómez et al 2011). A high degree of cytosine methylation has been found in P. pinea, which suggests a potential epigenetic regulation of gene expression and variation in phenotypic traits to improve the fitness of this species under different environmental conditions (Sáez-Laguna et al 2014). In fact, P. pinea is considered the most drought-resistant Mediterranean pine (Fady 2012).…”
Section: Introductionmentioning
confidence: 91%
“…A remarkable phenotypic plasticity in functional traits has also been described for stone pine when grown under restricted water availability conditions (Sánchez-Gómez et al 2011). A high degree of cytosine methylation has been found in P. pinea, which suggests a potential epigenetic regulation of gene expression and variation in phenotypic traits to improve the fitness of this species under different environmental conditions (Sáez-Laguna et al 2014). In fact, P. pinea is considered the most drought-resistant Mediterranean pine (Fady 2012).…”
Section: Introductionmentioning
confidence: 91%
“…However, this is a widespread species that grows under diverse environmental conditions, indicating that genetic variability does not entirely explain its adaptability (Vendramin et al, 2008;Soto et al, 2010). In fact, the successful adaptation of P. pinea seems to depend largely on the variability of phenotypic traits, which is high in this species (Mutke et al, 2010(Mutke et al, , 2013Sánchez-Gómez et al, 2011;Sáez-Laguna et al, 2014). Thus, phenotypic plasticity may explain the observed variability of the growth response to climate in different regions, that could suggest the capacity of P. pinea to adapt the annual distribution of cambial activity depending on site-specific climatic conditions.…”
Section: Spatiotemporal Variability Of Growth-climate Relationshipsmentioning
confidence: 99%
“…Epigenetic diversity can generate massive heritable variation of ecologically relevant plant traits such as root allocation, drought tolerance and nutrient plasticity (Zhang, Fischer, Colot, & Bossdorf, 2013), and it appears to increase the productivity and stability of plant populations in Arabidopsis thaliana under artificial conditions (Latzel et al., 2013). An increasing number of studies have also demonstrated the common existence and significant role of epigenetic variation in plant populations of herbs (Foust et al., 2016; Herrera, Medrano, & Bazaga, 2014; Medrano et al., 2014; Preite et al., 2015; Schulz, Eckstein, & Durka, 2014), shrubs (Avramidou, Ganopoulos, Doulis, Tsaftaris, & Aravanopoulos, 2015; Herrera & Bazaga, 2013, 2016), and trees (Guarino, Cicatelli, Brundu, Heinze, & Castiglione, 2015; Gugger, Fitz‐Gibbon, PellEgrini, & Sork, 2016; Lira‐Medeiros et al., 2010; Platt, Gugger, Pellegrini, & Sork, 2015; Sáez‐Laguna et al., 2014) under natural conditions. Therefore, epigenetic variation can be a very important mechanism for invasive plant success in a broad range of environments (Douhovnikoff & Dodd, 2014; Richards, Schrey, & Pigliucci, 2012).…”
Section: Introductionmentioning
confidence: 99%